Enhancing disability satisfaction through vocational training and inclusive programs: Evidence from pls-sem modeling - Siregar, Hairani; Suriadi, Agus; Amal, Bakhrul Khair (Research Journal in Advanced Humanities, 2025)
This study investigates the influence of vocational training effectiveness, disability independence, and program inclusivity on disability satisfaction. A quantitative approach was utilized, involving 150 respondents from various vocational training and inclusivity programs. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that vocational training effectiveness (β = 0.240, p < 0.05) and program inclusivity (β = 0.432, p < 0.001) have significant positive effects on disability satisfaction. These results highlight the critical role of tailored training programs and inclusive environments in enhancing the well-being and satisfaction of individuals with disabilities. However, the study found that disability independence does not significantly affect satisfaction (β = 0.120, p > 0.05). This suggests that vocational training and inclusivity may be more immediate drivers of satisfaction than independence alone. These findings underscore the importance of creating comprehensive policies that focus not only on skill development but also on promoting inclusivity in both vocational and broader social settings. Future research should explore additional mediators between disability independence and satisfaction and consider longitudinal studies to better understand these factors’ long-term impact on individuals with disabilities.